Data and welfare in credit markets - Jansen, Mark; Nagel, Fabian; Yannelis, Constantine; Zhang, Anthony Lee (Journal of Financial Economics, 2025)
We show how to measure the welfare effects arising from increased data availability. When lenders have more data on prospective borrower costs, they can charge prices that are more aligned with these costs. This increases total social welfare and transfers surplus across borrower types. We show that under certain assumptions the magnitudes of these welfare changes can be estimated using only quantity and price data. Applying our methodology to bankruptcy flag removal, we find that in a counterfactual world where bankruptcy flags are never removed from credit reports, previously-bankrupt borrowers’ surplus decreases substantially, whereas efficiency increases only modestly.